Análise documental das imagens fotográficas de romarias no Nordeste do Brasil - Elliott, Ariluci Goes [UNESP]; Madio, Telma Campanha de Carvalho [UNESP] (My University, 2013)
A discussion, through a literature review, on the use of photographic documents and Documentary Analysis (DA) for the preservation, description and retrieval of images of pilgrimages in northeastern Brazil, which are archived at the Laboratory of Information Science and Memory (LACIM). The photograph acts as an expression of faith and devotion; it is a witnesses and documents, through images, the records of the day-to-day folk religion in its multiple meanings and situations, linked to the sacred. The DA —as a set of procedures performed after the reading of documents— facilitates the analysed collection location or query through the documentary language. This paper tries to show that the particular form of the information contained in a photographic archive echoes submerged memories of the pilgrims, authenticating a social fact in the country, capturing the sacredness from specific moments of celebration.

En este trabajo se analiza, a través de una revisión de la literatura, el uso y el análisis documental (AD) de los documentos fotográficos para la preservación, descripción y recuperación de imágenes de peregrinaciones en el noreste de Brasil archivados en el Laboratorio de Ciencias de la Información y la Memoria (LACIM). La fotografía sirve como una expresión de fe y devoción; declara y documenta, a través de imágenes, los registros diarios de la devoción popular en sus múltiples significados y situaciones relacionadas con lo sagrado. El AD, como un conjunto de procedimientos realizados a partir de la lectura de documentos, facilita, a través del lenguaje documental, la localización o consulta de la colección analizada. Se intenta demostrar que la forma particular de la información contenida en un archivo fotográfico hace eco de los recuerdos de los peregrinos en la autenticación de un hecho social en el país; y permite captar lo sagrado de determinados momentos de la celebración.
Documentary analysis of photographic images of pilgrimages in Northeastern Brazil
Fotografias como documento de arquivo: uma discussão sobre os romeiros no nordeste do Brasil
Keywords: Archive; Brazil; Documentary analysis; Photography; Pilgrims